2020
DOI: 10.3390/ijms21186634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Life Stress on Bone Homeostasis in Mice and Humans

Abstract: Bone pathology is frequent in stressed individuals. A comprehensive examination of mechanisms linking life stress, depression and disturbed bone homeostasis is missing. In this translational study, mice exposed to early life stress (MSUS) were examined for bone microarchitecture (μCT), metabolism (qPCR/ELISA), and neuronal stress mediator expression (qPCR) and compared with a sample of depressive patients with or without early life stress by analyzing bone mineral density (BMD) (DXA) and metabolic changes in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 114 publications
(142 reference statements)
0
13
0
Order By: Relevance
“…In addition to shorter tails observed in LR animals, preliminary observations of shorter foot lengths in LR rats were observed in the current study, an observation that deserves further investigation. It is also important to note that, while stress and anxiety have been shown to negatively affect musculoskeletal tissue health and maturation (Ozturk et al, 2015;Foertsch et al, 2017;Wuertz-Kozak et al, 2020), musculoskeletal development is also well documented to be driven by mechanical stimulations, with reduction or removal of mechanical cues during development-resulting in 10.3389/fnbeh.2022.910056 underdeveloped musculoskeletal tissues (Connizzo et al, 2013;Galloway et al, 2013;Andarawis-Puri et al, 2015;Arvind and Huang, 2017). Therefore, it is difficult to separate whether the differences observed in musculoskeletal development in this study are attributable to varying neurobiological responses or mechanical loading environments, due to differences in bedding, mobility, body weight, or degree of play.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to shorter tails observed in LR animals, preliminary observations of shorter foot lengths in LR rats were observed in the current study, an observation that deserves further investigation. It is also important to note that, while stress and anxiety have been shown to negatively affect musculoskeletal tissue health and maturation (Ozturk et al, 2015;Foertsch et al, 2017;Wuertz-Kozak et al, 2020), musculoskeletal development is also well documented to be driven by mechanical stimulations, with reduction or removal of mechanical cues during development-resulting in 10.3389/fnbeh.2022.910056 underdeveloped musculoskeletal tissues (Connizzo et al, 2013;Galloway et al, 2013;Andarawis-Puri et al, 2015;Arvind and Huang, 2017). Therefore, it is difficult to separate whether the differences observed in musculoskeletal development in this study are attributable to varying neurobiological responses or mechanical loading environments, due to differences in bedding, mobility, body weight, or degree of play.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the impact of repeated restraint stress and maternal separation in mice (i.e., 6 h/day for PND 0-21), significant reductions in body weight and tail length were observed in the stressed animals, along with delays in eye-opening (Babu et al, 2012;Billakanti et al, 2012). Another study focusing on ELS in mice indicated disrupted bone innervation and metabolism, along with diminished levels of neuropeptide-Y and nerve growth factor, neurochemicals involved in osteoblast differentiation and sensory neural functions in bone, respectively (Wuertz-Kozak et al, 2020). In the same report, disruptions of anabolic bone metabolism were noted in humans following exposure to childhood adversity.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Both playing a musical instrument and playing sport produce brain adaptations that might affect sensory-motor functions (Bianco, Berchicci et al 2017). Neuronal stress might cause disturbing bone homeostasis (Schiavone, Morgese et al 2016, Camerino, Conte et al 2018, Huang, Hsu et al 2018, even tracking to early life stress (Wuertz-Kozak, Roszkowski et al 2020). Research on the prevention of the neuronal stress hopefully interfere with disturbance of bone homeostasis (Yang, Lu et al 2017, Lee, Mastronardi et al 2019, Wippert, Block et al 2019.…”
Section: Neuropsychological Effect On Bone Homeostasis With Musicians and Athleticsmentioning
confidence: 99%
“…1 B). When adult, the offspring has behavioural, cognitive and metabolic symptoms that persist across life and are transmitted to the offspring, via both females and males [32]–[39]. Phenotypes include risk-taking behaviours, depressive-like symptoms, altered social abilities, memory deficits, insulin/glucose dysregulation and altered bone homeostasis but also in some conditions, stress resilience and improved behavioural flexibility.…”
Section: Introductionmentioning
confidence: 99%